IMPLEMENTASI PEMBELAJARAN KITAB TA‘LIM AL-MUTA‘ALLIM DALAM PEMBENTUKAN AKHLAK SANTRI DI PONDOK PESANTREN ALKHAIRAAT MADINATUL ILMI DOLO - Zaitun (Paedagogia: Jurnal Pendidikan, 2019)
The purpose of this study is to describe the implementation or application of instructional books Ta‘lim al-Muta‘allim the moral formation of students at boarding school Alkhairaat Madinatul Ilmi Dolo. The qualitative method is used as a method of approach in this study by using observation data collection, interviews, and documentation are analyzed by using the method of data reduction, data presentation, and data verification. The research indicate is result of learning book Ta‘lim al-Muta‘allim is one book that discusses the presentation on moral learning that must be owned by the students in their studies. Terpokus description on what attitudes must be done by the students in studying good relationship with the teacher (Kiai), with fellow students, as well as how it should be enacting the books (the book) he learned it. In other words, this book is a guideline or code of conduct that students succeed in their studies either in accordance with laid down by Islam. By studying the book Ta'li m al-Muta'allim such, the students should be able to practice and broadcast both inside and outside the boarding school / community. As for the implementation of Learning book Ta‘lim al-Muta‘allim the moral formation of students at boarding school Alkhairaat Madinatul Ilmi Dolo is providing direct guidance of teaching through the book, namely by providing appropriate role models that are suggested or taught by the book Ta‘lim al-Muta‘allim. Therefore, application of the Book Ta‘lim al-Muta‘allim between teachers and students in learning is usually not optimal, the influence of the factors of teachers, for example exemplary. So, it should be an important practice, not only wants his students to master learning the book but have a direct practice.